Organizational agility in the digital era: A systematic review and scientometric analysis - Flores Quiñonez, Frank Antonio (2025)
Agility has emerged as a critical factor for business competitiveness in dynamic and volatile environments. This study presents a systematic review and scientometric analysis of recent literature on agility, based on Scopus data from 2020 to 2024. The methodology includes defined inclusion and exclusion criteria for document selection, a co-occurrence analysis of key terms, and an evaluation of current trends in academic literature. Key themes identified include the impact of agile leadership, digital transformation, emerging technologies, and organizational resilience. The findings reveal a strong interconnection between agility, innovation, and sustainability, emphasizing the role of dynamic capabilities and collaborative ecosystems in generating competitive advantages. The study concludes that adopting agile strategies enables organizations to respond effectively to crises and disruptions, thereby ensuring their sustainability and growth in globalized markets.